AB0684 A review of temporal artery biopsies at a district general hospital. (12th June 2018) - Yusuf, M.A.; Al-Zaza, M.; Walton, T.
Abstract : Background: Giant cell arteritis is the most common vasculitis in the western world in the over 50 population. The morbidity associated with its natural progression and treatment is significant. No single investigation has been identified to accurately confirm or reject its diagnosis, though for some years biopsy of the superficial temporal artery has been carried out to support the diagnostic process. More recently, doppler ultrasound of the artery has gained prominence, though its widespread use is limited. Temporal artery biopsy (TAB) is a significant use of resources, involving a surgeon and their team, as well as a histopathologist. It is an invasive procedure with the risks that this entails. It behoves the referring doctor to ensure that the probability of a positive result is as high as practicable. Objectives: To determine the factors providing the highest likelihood of a positive TAB result. Methods: The notes of all patients undergoing a TAB during a 3 year period 2013–2016 were requested from the Medical Records department at a district general hospital. The first 100 of these were reviewed by the authors. Each set of notes was examined for the following: - Demographics (sex, age) - The first department the patient was referred to (Rheumatology/Ophthalmology/Neurology/direct from the General Practitioner to Vascular Surgery) - Period of time from symptom onset to biopsy - Period of time on steroids to biopsy - Initial dose of steroids prescribed - Pre-treatment ESR - Pre-treatment CRP - Presence of symptoms (headache/jaw claudication/polymyalgia rheumatica) - Other causes for a raised ESR - The pre-test probability of a positive TAB result as assessed by the reviewer - TAB result as reported by local histopathologist - Evidence of the biopsy result impacting treatment Results: Of the 100 TAB's reviewed, 16 yielded positive results (16%). A breakdown of the notes review for these patients is included in the following table: Conclusions: This study has shown that less than a fifth of TAB's conducted during this period at our district general hospital yielded a positive result. There is scope to improve this yield significantly if we identify candidates for TAB better. There was no positive result for any of the 16 patients less than 58 years of age. The majority had a raised CRP and ESR, though one patient had a CRP of 2. This reflects the need for vigilance before discounting GCA as a diagnosis. One patient had a positive TAB even after 28 days of prednisolone 40 mg daily. The majority (14/16) had their biopsy within 3 weeks of steroid initiation, indicating that a short delay in biopsy does not rule out a positive result. This study will help us develop a local pathway including Ophthalmology, Neurology, Vascular Surgery and Primary Care to improve the yield of positive TAB. This will improve patient experience as well as ensure appropriate use of resources. Disclosure of Interest: None declared